Fragile and robust dual image watermarking based on DWT-SVD - Ernawan, Ferda; Gen, Lim Chen; Suraya, Abu Bakar; Chuin, Liew Siau; Azamuddin, Ab Rahman (Institute of Electrical and Electronics Engineers Inc., 2024)
Digital media faces significant challenges related to unauthorized access, manipulation, and copyright infringement, necessitating effective authentication and copyright protection mechanisms. This research suggests a dual watermarking scheme based on the DWT-SVD and two authentication layers to identify tamper localization. A watermark was inserted by a set of rules for modifying U (2,1) and U (3,1) of DWT-SVD for the robustness watermarked image. The robust watermarked image can carry ownership and copyright information. The watermarked image is then inserted with two authentication bits into the least significant bit (LSB) which is highly sensitive to any modifications or tampering. The authentication bits are obtained from the different average sub-block 3x3 pixels with an image block of 6x6 pixels and parity bits of the sub-block image. Two authentication bits can be used to authenticate the integrity of the watermarked image. The results demonstrate its effectiveness in providing robust copyright protection and authentication capabilities. The scheme exhibits high imperceptibility, preserving the visual quality of the watermarked content with an average PSNR value of 45db, while ensuring a high level of originality to unauthorized alterations. Additionally, the proposed scheme achieved robustness with an NC value of about 0.981 against tampering rates up to 50%.